Drug-induced lupus: Including anti-tumour necrosis factor and interferon induced. (May 2014) - Araújo-Fernández, S; Ahijón-Lana, M; Isenberg, DA
Drug-induced lupus erythematosus is defined as a syndrome with clinical and serological features similar to systemic lupus erythematosus that is temporally related to continuous drug exposure and which resolves after discontinuation of this drug. More than 90 drugs, including biological modulators such as tumour necrosis factor-α inhibitors and interferons, have been identified as likely 'culprits'. While there are no standard diagnostic criteria for drug-induced lupus erythematosus, guidelines that can help to distinguish drug-induced lupus erythematosus from systemic lupus erythematosus have been proposed and several different patterns of drug-induced lupus erythematosus are emerging. Distinguishing drug-induced lupus erythematosus from systemic lupus erythematosus is important because the prognosis of drug-induced lupus erythematosus is usually good when the drug is withdrawn. This review discusses the differences between drug-induced lupus erythematosus and systemic lupus erythematosus, the mechanisms of action of drug-induced lupus erythematosus and drugs that are usually associated with drug-induced lupus erythematosus, with particular focus on the biological treatments.